2011
DOI: 10.5483/bmbrep.2011.44.9.578
|View full text |Cite
|
Sign up to set email alerts
|

A replication study of genome-wide CNV association for hepatic biomarkers identifies nine genes associated with liver function

Abstract: Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) are biochemical markers used to test for liver diseases. Copy number variation (CNV) plays an important role in determining complex traits and is an emerging area in the study various diseases. We performed a genome-wide association study with liver function biomarkers AST and ALT in 407 unrelated Koreans. We assayed the genome-wide variations on an Affymetrix Genome-Wide 6.0 array, and CNVs were analyzed using HelixTree. Using single linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Consistent with previous studies, the hepatic histological damage was observed in DSS-induced murine colitis model ( 43 , 44 ). AST and ALT always seemed like sensitive indicators to access the hepatic damage ( 45 , 46 ). Here our results revealed the increased plasma and hepatic levels of AST and ALT in acute colitis mice.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, the hepatic histological damage was observed in DSS-induced murine colitis model ( 43 , 44 ). AST and ALT always seemed like sensitive indicators to access the hepatic damage ( 45 , 46 ). Here our results revealed the increased plasma and hepatic levels of AST and ALT in acute colitis mice.…”
Section: Discussionmentioning
confidence: 99%
“…The VCS tool provides a graphical view of the physical distribution of CNV or SNP on chromosomes. Any marker contained information of chromosomal position by point (SNP) or specific ranges (CNV, miRNA, and repeat sequence) can be used in this tool ( Kim et al, 2010 ; 2011 ; 2013 ). This menu is useful for comparing the physical distribution of your own CNV or SNP.…”
Section: Program Overviewmentioning
confidence: 99%
“…It manifests divergent expression patterns in conditions such as pulmonary adenocarcinoma (9) and cerebral glioma (10) , demonstrating a correlation with immune in ltration within tumour cells. Concurrently, extant studies have shown an association between PSMC6 and aspartate aminotransferase (AST), indicating that PSMC6 is a pivotal factor in uencing disease onset within the hepatic milieu (11) . Nevertheless, the PSMC6 domain remains a lacuna in HCC.…”
Section: Introductionmentioning
confidence: 99%